Dynamic externalities of basic medical insurance compensation, health capital accumulation, and economic growth - Yuan, Xinyue; Yang, Xujin (Frontiers in Public Health, 2025)
BackgroundA strong healthcare system plays a vital role in reducing the financial burden on households while simultaneously promoting sustainable economic development. This study investigates how dynamic medical insurance compensation affects health capital accumulation and economic growth, thereby revealing the broader economic implications of health policy design.MethodsThis paper develops a neoclassical economic growth model that incorporates dynamic basic medical insurance and health capital. Utilizing the shooting algorithm, we compute equilibrium solutions at each period along the saddle path and analyze the external effects of different compensation strategies. This approach enables a systematic evaluation of how varying the compensation rate influences welfare, labor allocation, and long-term growth trajectories.ResultsThe absence of medical insurance compensation or a constant compensation rate leads to a decline in welfare over time. In contrast, a progressively decreasing compensation rate significantly promotes the consumption of healthcare goods, increases health capital, and stimulates economic growth. The model also shows that this compensation design enhances overall welfare along the transition path and induces a partial reallocation of labor toward the healthcare sector.ConclusionsThe findings highlight the importance of dynamic, policy-responsive compensation structures in maximizing long-term welfare. A gradually declining medical insurance compensation rate not only improves population health and boosts economic output but also provides a viable strategy for labor market optimization and health system sustainability. These insights offer valuable guidance for health policy reform in developing and transitioning economies.